Compressed 3D and 2D digital images versus standard 3D slide film for the evaluation of glaucomatous optic nerve features. Issue 3 (23rd August 2017) - Sandhu, Simrenjeet; Rudnisky, Chris; Arora, Sourabh; Kassam, Faazil; Douglas, Gordon; Edwards, Marianne C; Verstraten, Karin; Wong, Beatrice; Damji, Karim F
Abstract : Synopsis: Clinicians can feel confident compressed three-dimensional digital (3DD) and two-dimensional digital (2DD) imaging evaluating important features of glaucomatous disc damage is comparable to the previous gold standard of stereoscopic slide film photography, supporting the use of digital imaging for teleglaucoma applications. Background/aims: To compare the sensitivity and specificity of 3DD and 2DD photography with stereo slide film in detecting glaucomatous optic nerve head features. Methods: This prospective, multireader validation study imaged and compressed glaucomatous, suspicious or normal optic nerves using a ratio of 16:1 into 3DD and 2DD (1024×1280 pixels) and compared both to stereo slide film. The primary outcome was vertical cup-to-disc ratio (VCDR) and secondary outcomes, including disc haemorrhage and notching, were also evaluated. Each format was graded randomly by four glaucoma specialists. A protocol was implemented for harmonising data including consensus-based interpretation as needed. Results: There were 192 eyes imaged with each format. The mean VCDR for slide, 3DD and 2DD was 0.59±0.20, 0.60±0.18 and 0.62±0.17, respectively. The agreement of VCDR for 3DD versus film was κ=0.781 and for 2DD versus film was κ=0.69. Sensitivity (95.2%), specificity (95.2%) and area under the curve (AUC; 0.953) of 3DD imaging to detect notching were better (p=0.03) than for 2DD (90.5%; 88.6%; AUC=0.895). Similarly, sensitivity (77.8%), specificity (98.9%) and AUC (0.883) of 3DD to detect disc haemorrhage were better (p=0.049) than for 2DD (44.4%; 99.5%; AUC=0.72). There was no difference between 3DD and 2DD imaging in detecting disc tilt (p=0.7), peripapillary atrophy (p=0.16), grey crescent (p=0.1) or pallor (p=0.43), although 3D detected sloping better (p=0.013). Conclusions: Both 3DD and 2DD imaging demonstrates excellent reproducibility in comparison to stereo slide film with experts evaluating VCDR, notching and disc haemorrhage. 3DD in this study was slightly more accurate than 2DD for evaluating disc haemorrhage, notching and sloping.